Industrial training report: Pejabat Tanah dan Jajahan Machang / Nur Alesya Ismail - Ismail, Nur Alesya (Universiti Teknologi MARA, Perlis, 2024)
This report is about my internship program at Pejabat Tanah dan Jajahan Machang (PTJM). Through this report I discussed about the details of the company, my observation for swot matrix regarding to this company and my experienced and skills during my internship. First and foremost, I include my resume and details of the company including their background, organization structure, vision, mission, objective. During my internship I was assigned to the Administration and Finance Department. As for my department we manage and handle all the employees in this company. I also include what I manage to improve along with my working experince and skills development. In addition, I was assigned to identify the swot matrix for this company in able to provide the the recommendation for the company. In this swot matrix there were a few strategis that can help PTJM improve their company. Last but not least, the focus of my internship is to learn and experienced the real working environment and doing the hands-on tasks within the date given. I also get the opportunity to apply the knowledge and skills that I have learned duting mu studies.